(untitled) (Research, Society and Development, 2025)
Independent (external) audits are a support tool for shareholders, investors and regulatory bodies. Its scope has expanded with the application of ESG (Environmental, Social and Governance) concepts. Legal tools for holding companies accountable under the Polluter Pays Principle are strengthening and generating demand for independent audits. This article aims to present and justify the creation of a new branch in environmental auditing, highlighting its relevance, theoretical foundation, applicability, and contributions to enhancing environmental assessment and management. In Brazil, tailing dam failures resulted in large-scale socio-environmental and economic impacts, leading to legislative responses to minimize impacts and prevent new emergencies. In 2019, the Public Prosecutor’s Office of Minas Gerais worked with environmental agencies to hold the responsible mining company accountable, signing a Term of Covenant (TC Fauna) to ensure the welfare of animals affected by environmental disasters, with the intervenience of an external technical audit to monitor the established commitments. Animal Protection Audit is integrated with the Environmental Audit by assessing compliance with legal guidelines, techniques and good environmental management practices, while acting to mitigate impacts on the health and welfare of wildlife and domestic animals.